Juridical Review of Multiple Certificate Dispute Resolution as Proof of Land Ownership RightsIn Pati Regency - Prasetya, Brian Rizqi (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
Soil is very closely related to human life. Everyone certainly needs land, in fact land has such an important position for humans, that it gives rise to the desire to control and own it. This sense of wanting to own will ultimately give rise to land disputes. One of the problems is the emergence of double (overlapping) certificates. Double certificates are certificates for the same plot of land. So, one plot of land with 2 (two) or more certificates with different data. This type of research is sociological juridical law by means of a survey, namely research that takes data directly from the population using data collection tools, namely questionnaire interviews, after which the data is taken and processed to obtain conclusions using a deductive method. Meanwhile, if we look at its nature, this research is descriptive, namely research that explains in the form of clear and detailed sentences. Factors that cause double certificates include, a. Land registration map not yet available. b. BPN does not yet have a single map, c. Land/location sizes overlap. d. there is an element of fraud. Resolving Dual Certificate Issues can be done through mediation or litigation (court), and the settlement is taken by the Pati City Land Office.